Manajemen Pondok Pesantren dalam Pembentukan Sikap Kemandirian Santri di Pondok Pesantren Ell-Futhah Bulupayung - Ratnawulan, Teti; Hidayat, Ayi Najmul; Mugiarto, Mugiarto; Chamidi, Agus Salim (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to describe and analyze in depth the management of the boarding school in the formation of attitudes of self-reliance of students in the Boarding school Ell-Futhah Bulupayung, start from planning, organizing, implementation, monitoring and evaluation of the program. This study is a field research with qualitative approach. Data collection techniques using observation, documentation and interviews. The data analysis uses interactive model consisting of data collection, data reduction, data presentation, and conclusion. Examination of the validity of data persistence observation, and triangulation methods. The results showed that the management of education in the program of formation of the attitude of self-reliance of students in the Boarding school Ell-Futhah Bulupayung conducted with four stages, namely (1) Planning already existed before independence programs were implemented such as the procurement of meeting, selection of program self-reliance, and other. The planning stage includes: planning the curriculum, teaching materials, personnel, facilities and infrastructure, as well as program planning; (2) The Organization implemented with the involvement of the elements of boarding schools such as the chaplain, coach, instructor and all elements to help organizing the program of the independence of the students has been running well although there are still lack of human resources because the division of tasks is still stacked and the number of students who follow the activities of the skills in the boarding school; (3) The Implementation of the program was implemented with several stages in which carry out teaching and learning activities, organizational activities of the compulsory routine of the boarding school, individual activities of students day-to-day, activity support, and rules of discipline of the lodge; (4) Supervision and evaluation of the program, caretakers and administrators along with the community participated in evaluating such activities. If there is a weakness, then it will be given input for improvement in the future. Keywords: Planning, Organizing, Implementation, Monitoring and Evaluation of the Program, the Independence of Students